Native Subsistence Fisheries: A Synthesis of Harvest Studies in Canada - Berkes, Fikret (ARCTIC, 1990)
Subsistence fisheries, as distinct from commercial and recreational, exist throughout much of the Canadian North and satisfy local needs for fish protein. These fisheries have been investigated quantitatively only since the 1970s. Many of these studies are in the "grey literature"; methods of study and reporting are not standardized, and interpretation of data is often problematic. Nevertheless, some generalizations can be offered from a preliminary survey of harvest study data from 93 communities and from 10 regional studies representing Labrador, Quebec, Ontario, Manitoba, Saskatchewan, British Columbia and the Northwest Territories. The data indicate a wide range of harvest values, clustering at about 60 kg of whole fish per capita per year. If these data are representative, there is a significant subsistence fishery sector important for the local economies of hundreds of communities. Most of these fisheries are not being reported in fishery statistics, nor are they being monitored and assessed.